The Effect of the Internet on Enhancing Marketing among Business Organizations - Sarkar Ahmed Saeed; Savo Rezhan Abas; Nada Bashir Abdalkarim (Research Synergy Foundation, 2023)
The profitability of business organizations greatly relies on utilizing the Internet for marketing purposes. Through careful and knowledgeable use of the Internet, organizations can improve various aspects of their operations, mainly marketing. This study examines the Internet's specific impact on business organizations' marketing strategies. This study aims to enhance our understanding of how Internet usage impacts effective Internet management and its potential to boost marketing efforts for businesses in achieving their goals. The study highlights the advantages of using the Internet in business, differentiating organizations that utilize it from those that do not. Additionally, it emphasizes how the Internet can make long-term tasks more manageable and less time-consuming. Using the Internet can take you to levels that may have once been just a fantasy since the beginning of your business. In this paper, we have used the relevant literature mainly about the effects of using the Internet for a business organization, such as gaining more customers, increasing profits, reaching an infinite limit, and finally succeeding. Marketing, Internet, business organization, customer, attract customer.